The influence of digit size and proportions on dexterity during cold exposure. Issue 4 (20th April 2018) - Payne, Stephanie; Macintosh, Alison; Stock, Jay
Abstract: Objectives: The current study investigated whether size and proportions of the hands and digits affect dexterity during severe cold exposure. As wide hands are known to lose less heat than narrow hands, and narrow digits are associated with greater dexterity, this study aimed to test whether there was a direct trade‐off between dexterity and thermoregulation that shapes hand morphology. Methods: Participants (25 women, 15 men) carried out the Purdue Pegboard test before and after a 3‐min ice‐water immersion of the hand. Their hand length, hand width, digit lengths, and digit widths were measured using standard anthropometric methods. Results: Wide first and third digits associated with significantly reduced dexterity after immersion relative to individuals with narrower first and third digits. Second digit width positively correlated with average digit temperature after immersion. Hand length and hand width did not influence dexterity. Conclusion: The current study suggests that digit width influences dexterity in cold conditions, reflecting patterns found at room temperature. Hand and digit morphology may be the product of two significant constraints on the hand: dexterity and thermoregulation. In cold conditions, hand morphology appears to be predominantly constrained by thermal stress, at the expense of dexterity. This may have important implications for interpreting the morphology of extinct and extant hominins.